2021
DOI: 10.3390/healthcare9070788
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus—A Risk Factor for Unfavourable Outcome in COVID-19 Patients—The Experience of an Infectious Diseases Regional Hospital

Abstract: Early research into the implications concerning the evolution of the infection caused by the new coronavirus in people with glucose metabolism dysfunction, in this case diabetics, shows that severe forms of the disease predominate in this risk category. Moreover, it seems that even in patients with normal glycaemic status, COVID-19 may predispose to the development of hyperglycaemia which modulates immune mechanisms and inflammatory responses, with direct effects on morbidity and mortality. Thus, taking into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…All operated patients also had antibiotic therapy, making it difficult to determine the separate involvement of urological maneuvers or antibiotic therapy in the occurrence of MDR UTIs; both probably play a role. The presence of diabetes, renal failure, anemia, and neoplasia has also been noted in other studies [ 22 , 23 ]. The longer hospital stay in CoV patients can be explained by the additional risk of CoV infection, which prolonged the evolution of the MDR UTI [ 16 , 24 ], and by the fact that more CoV patients presented with urosepsis, and therefore had more severe forms of MDR UTIs.…”
Section: Discussionsupporting
confidence: 69%
“…All operated patients also had antibiotic therapy, making it difficult to determine the separate involvement of urological maneuvers or antibiotic therapy in the occurrence of MDR UTIs; both probably play a role. The presence of diabetes, renal failure, anemia, and neoplasia has also been noted in other studies [ 22 , 23 ]. The longer hospital stay in CoV patients can be explained by the additional risk of CoV infection, which prolonged the evolution of the MDR UTI [ 16 , 24 ], and by the fact that more CoV patients presented with urosepsis, and therefore had more severe forms of MDR UTIs.…”
Section: Discussionsupporting
confidence: 69%
“…This result supports the findings of a previous meta-analysis study of 1382 diabetic patients by Roncon et al, (14), who reported that COVID-19 patients who were diabetic had a significantly increased risk of ICU admission as compared to non-diabetic patients. In another study, Miftode et al (15) indicated that COVID-19 patients with diabetes have a threefold greater risk of death and 1.5 fold increased risk of developing severe form of acute respiratory failure in comparison to nondiabetics. The association of diabetes to severity of infection has been made to the increased glucose levels in blood as well as respiratory secretions enabling the virus to multiply faster in cells (16) Multivariate analysis of hematological parameters in this study highlighted that increased D-dimer, Ferritin and NLR as independent predictors for severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior work has shown that even in cases of well-controlled pre-existing diabetes, hyperglycemia was commonly observed in acutely ill hospitalized patients and linked to adverse outcomes [44,45]. It seems that COVID-19 may lead to high blood glucose levels in patients with normal glycemic status by modulating immune and inflammatory responses, directly affecting morbidity and mortality [46][47][48]. In a study by Charoenngam et al in patients without a history of diabetes, hyperglycemia on the day of admission was shown to have a statistically significant association with mortality, ICU admission, intubation, acute kidney injury, and severe sepsis/septic shock, after adjusting for potential confounders.…”
Section: Discussionmentioning
confidence: 99%